Du placement de produit à l’artistisation par réaction inverse. Analyse socio-sémiotique du film Logorama - Julien Péquignot (Communiquer)
Starting from Logorama, an animated short film entirely made out of logos, the paper investigates induced meaning productions. From a pragmaticist point of view, combining semiopragmatic, artwork sociology and Peirce’s semiotic, enunciation traces are examined in order to rebuild the actual semiotizations in this particular case of use and this readjustement of advertising artefacts, and to determine their singularity.